Technical variability partially explains success at the Paris 2024 Olympic and Paralympic Games - Kons, R. L.; de OS Gulias, V.; Detanico, D. (International Journal of Sports Science & Coaching, 2025)
Research on performance variability in judo particularly at the Olympic and Paralympic levels have provided valuable insights, especially regarding technical-tactical aspects of elite athletes. Building on this perspective, this study aimed to examine whether variability in standing and groundwork techniques could predict performance (measured by win ratios) in judo athletes competing at the Paris 2024 Olympic and Paralympic Games. Data were obtained from official match records published in the Official Result Books at the Paris 2024 Olympic and Paralympic Games. For each athlete, variability in both standing and groundwork techniques was calculated. A multiple linear regression analysis was conducted to assess the relative contributions of technical variability in these domains to competitive success (win ratio) with a significance level set at 5%. The findings revealed that variability in standing techniques accounted for 59% of the win ratio in Olympic athletes, while groundwork variability explained 33%. In Paralympic athletes, standing variability contributed 59%, and groundwork variability accounted for 37%. These factors together explained 47% and 56% of the win ratios in Olympic and Paralympic judo, respectively. The results highlight the importance of technical variability as a key factor in competitive success, particularly in adapting to dynamic match conditions.